Retention costs of periodontally compromised molars in a German population. (4th March 2016) - Schwendicke, Falk; Plaumann, Anna; Stolpe, Michael; Dörfer, Christof E.; Graetz, Christian
Abstract: Aim: This study assessed the long‐term costs per retention year for periodontally affected molars. Methods: A cohort of 379 compliant subjects was retrospectively evaluated. Periodontal, restorative, endodontic, prosthetic and surgical treatment costs were estimated based on fee items of the private German health insurance. Costs/year were calculated and the impact of tooth‐ and subject‐related factors on this cost‐effectiveness ratio assessed using generalized linear‐mixed modelling. Results: 2306 molars received non‐regenerative initial and supportive therapy and were followed until extraction or censoring (in mean (SD): 16.5 [6.8] years). Per year, 0.07 (SD: 0.12) deep scalings, 0.04 (0.11) open flap debridements, 0.01 (0.04) resective therapies and 2.49 (0.12) SPTs had been provided. Few teeth received non‐periodontal treatments. Costs/year decreased significantly with each tooth a patient had at baseline (mean difference: −0.01, 95% CI: −0.02/−0.01 Euro/year), and increased with each mm of probing‐pocket depth (0.04 [0.03/0.06] Euro/year), in upper (0.07 [0.11/0.31] Euro/year) or mobile molars (up to 0.33 [0.18/0.48] Euro/year), those with bone loss (up to 0.11 [0.04/0.17] Euro/year), endodontic treatment (0.24 [0.15/0.33] Euro/year), peri‐apical lesions (0.24 [0.11/0.38]) and prosthetic treatment (0.54 [0.49/0.59] Euro/year). Conclusions: Annual costs for retaining periodontally affected molars were limited, and associated mainly with tooth‐level factors.